Charged gravastars with conformal motion in the Finslerian space-time - T. Sanjay; S. K. Narasimhamurthy; Z. Nekouee; H. M. Manjunatha (European Physical Journal C: Particles and Fields, 2024)
Abstract In this article, we investigate the charged gravastar under conformal motion with the background of Finsler geometry. Mazur and Mottola pioneered the concept of the gravastar (gravitational vacuum star) for the first time. This vacuum object consists of three distinct regions, that is, (i) interior de Sitter region, (ii) thin shell consisting of ultrarelativistic stiff, and (iii) exterior vacuum Schwarzschild region. The nature of these regions can be analyzed by considering different equations of state parameters. We have studied various physical features of the gravastar, such as length, energy, entropy, stability, and the adiabatic index, both graphically and analytically within the Finslerian framework. Also, we have obtained the exact and non-singular solution for the gravastar model.